Noah's flood the Genesis story in Western thought - Cohn, Norman 1915-2007 (Yale Univ. Press, 1996)
From the late eighteenth century until the present day the story of Noah's Flood has been involved also in the conflict between traditional religious beliefs and science and the attempts to harmonize the two. Cohn describes how, while geological and palaeontological discoveries were calling the historicity of the Flood into question, fundamentalists have continued to champion it, even to the extent of searching for the landing site of the ark. Finally, he considers how, in the course of the present century, the story has been interpreted as a solar myth, a lunar myth, a fertility myth, and even (psychoanalytically) as an expression of male resentment against women. Wide ranging and compellingly narrated, the book includes intriguing accounts of the scholars and theologians who endorsed or rejected the Flood story and contributed to its powerful resonance over two thousand years